Synthesis of Dioxo-Dioxane and Dioxo-Dioxepane Ethyl Oleate Derivatives as Bio-Lubricant Base Stocks - Tutik Dwi Wahyuningsih; Yehezkiel Steven Kurniawan (Indonesian Journal of Chemistry, 2020)
In this study, two novel compounds, i.e., ethyl 8-(3-octyl-5,6-dioxo-1,4-dioxan-2-yl)octanoate and ethyl 8-(3-octyl-5,7-dioxo-1,4-dioxepan-2-yl)octanoate were prepared from oleic acid as the starting material. Both compounds were obtained from the esterification of the ethyl 9,10-dihydroxyoctadecanoate with dicarboxylic acids in the presence of p-toluenesulfonic acid as a catalyst. The chemical structures of the synthesized products were confirmed by FTIR, 1H-NMR, and MS spectrometers. The bio-lubricant properties of the products, such as density, total acid number, total base number, and iodine value, were determined and the effect of the dioxane and dioxepane heterocyclic rings to their bio-lubricant properties was discussed. The esterification of ethyl 9,10-dihydroxyoctadecanoate with oxalic acid gave ethyl 8-(3-octyl-5,6-dioxo-1,4-dioxan-2-yl)octanoate compound in 93.9% yield, while the esterification of ethyl 9,10-dihydroxyoctadecanoate with malonic acid gave ethyl 8-(3-octyl-5,7-dioxo-1,4-dioxepan-2-yl)octanoate compound in 89.6% yield. The density and total base number of the products were close to the standard commercial lubricant values. Meanwhile, the total acid number and the iodine value of the ethyl 8-(3-octyl-5,6-dioxo-1,4-dioxan-2-yl)octanoate were smaller than the standard commercial lubricant, showing that this compound is a promising bio-lubricant in a real application.